HIV-AIDS e co-morbidades não infecciosas : alterações ósseas, renais metabólicas em pacientes infectados pelo HIV-1 atendidos em serviço de assistência especializada em Vitória, ES - Pinto Neto, Lauro Ferreira da Silva (2012)
The increase in life expectancy achieved following modern antiretroviral exposes the HIV-infected population to non-infectious co-morbidities that worsen with ageing. The aim of this work was to study prevalence for renal, bone and metabolic disturbances and associated factors among HIV infected patients in an AIDS outpatient clinic. Urine samples exams, creatinine, glucose and lipids measurements, assessment of cardiovascular risk, HIV viral load, TCD4/TCD8 cell count and were done in patients attended by specialized assistance service at Santa Casa de Vitoria. Bone mineral density by dual-energy x-ray absorptiometry was performed at CEDOES (Center for Diagnostic and Research on Osteoporosis of Espirito Santo). Four papers were written based in project’s results: a case report of spontaneous supracondylar femur fracture in a patient with well controlled HIV viral load; an original report of low bone mineral density among 54,7% out of 300 patients, associated with menopause, male gender and body mass index bellow 25; another report of 40,6% of urinary abnormalities and 9,8% of reduced glomerular filtration out of 254 patients, the later one associated with black race, arterial hypertension, age above 50 years, proteinuria and hematuria; and a report of diabetes, impaired glucose tolerance and cholesterol disturbances among 5,8%, 28,5% and 22,3%, respectively, out of 498 HIV treated patients, the later one associated with lopinavir/r therapy. We conclude that clinical management of those age related diseases is essential for appropriate treatment of HIVinfected patients.